Cloning and expression of a human papillomavirus 18 l1 gene isolated from a Cuban patient in Escherichia coli - Pimienta, Elsa; RodrÃguez, Sandra; Fando, Rafael; Otero, Adriana; Serrano, Yunier; Ortega, Darien; Palenzuela, Ariel; Marrero, Karen (Revista Cubana de Medicina Tropical, 2018)
Introduction: Human papillomavirus (HPV) vaccines are based on the L1 major capsid protein, which forms the pentameric assembly unit of the viral shell. Objectives: To clone a HPV-18 l1 gene from a Cuban female patient and to express the full-length and deletion variants of the HPV-18 l1 gene in Escherichia coli, for further vaccine preparation studies. Methods: The wild-type HPV-18 l1 gene was amplified by PCR from a cervical lesion sample of a Cuban patient and subsequently, it was subcloned into pET26b and pET28a vectors. Three deletion mutants were constructed using PCR based on the HPV-18 l1 gene, which encode truncated proteins lacking 30 amino acids at the C-terminus in combination with 5, 6 or any deleted residue at the N-terminus. Results: The cloned HPV-18 l1 gene had the highest level of sequence similarity (99.9%) to the African variant EF202152. The C-terminal 30 amino acid truncated HPV-18 L1 was produced at similar levels than the HPV-18 L1s truncated at both ends. The three L1 variants had similar solubility profiles, with a percentage higher than 50 % in the soluble fraction of E. coli SHuffle C3026. Conclusion: The results of this work suggested that the truncation of thirty amino acid residues at the C-terminus of the HPV-18 L1 had a major contribution to the expression of a wild HPV-18 l1 gene in E. coli. Thus, a C-terminal 30 amino acid truncated HPV-18 L1 could be suitable for preparing a HPV vaccine to prevent persistent HPV infections and cervical cancer in Cuba.